2006
DOI: 10.1124/mol.106.023762
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Kinetics of Xanomeline Binding and Selectivity of Activation of G Proteins at M1 and M2 Muscarinic Acetylcholine Receptors

Abstract: Xanomeline is a functionally selective M 1 /M 4 muscarinic acetylcholine receptor agonist that nevertheless binds with high affinity to all five subtypes of muscarinic receptors. A novel mode of interaction of this ligand with the muscarinic M 1 receptors characterized by persistent binding and receptor activation after extensive washout has been shown previously. In the present study, using human M 1 and M 2 receptors expressed in Chinese hamster ovary cells and [3 H]N-methylscopolamine as a tracer, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
70
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 23 publications
8
70
0
Order By: Relevance
“…Since xanomeline is not entirely M 1 /M 4 -specific (Jakubík et al, 2006;Noetzel et al, 2009), classical cholinomimetic side effects, e.g., gastrointestinal side effects, were observed in humans (Bodick et al, 1997;Shekhar et al, 2008). Previous efforts to develop highly selective orthosteric agonists of the individual muscarinic subtypes have not been successful.…”
Section: Discussionmentioning
confidence: 99%
“…Since xanomeline is not entirely M 1 /M 4 -specific (Jakubík et al, 2006;Noetzel et al, 2009), classical cholinomimetic side effects, e.g., gastrointestinal side effects, were observed in humans (Bodick et al, 1997;Shekhar et al, 2008). Previous efforts to develop highly selective orthosteric agonists of the individual muscarinic subtypes have not been successful.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its reversible interaction with the classical orthosteric binding site of the M 1 mAChR, xanomeline also binds persistently to a secondary site(s) on the receptor [2,3]. This wash-resistant binding occurs almost instantaneously at the M 1 , but not the M 2 mAChR [7], which suggests induction of receptor subtype-specific conformations by xanomeline. This receptor subtype selectivity and the lack of similar effects when liposomes are treated with xanomeline prior to reconstitution of M1 receptors [8] support a receptor specific mechanism.…”
mentioning
confidence: 99%
“…These findings also strongly argue against the possibility of membrane lipids serving as a nonspecific depot of xanomeline where xanomeline leeches out to rebind to the receptor causing persistent activation. It has been shown that persistent xanomeline binding to the M 1 mAChR acutely modulates binding of ligands to the orthosteric site in an allosteric manner [2,7,9]. It also causes wash-resistant receptor activation that is silenced by atropine [2].…”
mentioning
confidence: 99%
“…Wash-resistantly bound xanomeline activates guanosine 5Ј-O-(3-thio)triphosphate binding at the M 1 receptor, and, although with lower efficacy but similar affinity, also at the M 2 receptor (Jakubík et al, 2006). Likewise, wash-resistantly bound xanomeline induces durable antagonism of M 5 receptor activation (Grant and El-Fakahany, 2005).…”
mentioning
confidence: 99%
“…3-[3-Hexyloxy-1,2,5-thiadiazo-4-yl]-1,2,5,6-tetrahydro-1-methylpyridine (xanomeline) is an atypical agonist that binds to all muscarinic receptor subtypes with high affinity (Bymaster et al, 1997;Watson et al, 1998;Wood et al, 1999;Jakubík et al, 2006), but it displays functional selectivity for the M 1 and M 4 receptors (Shannon et al, 1994;Ward et al, 1995;Bymaster et al, 1997Bymaster et al, , 1998. Xanomeline was supposed to be developed as an M 1 receptor-selective drug for treatment of Alzheimer's disease.…”
mentioning
confidence: 99%